The effect of emotional intelligence on police officers work-life balance: The moderating role of organizational support - Kumarasamy, Morkana Muthu; Pangil, Faizuniah; Mohd Isa, Mohd Faizal (SAGE Publications, 2016)
Work–life balance is a main concern for employees and employers alike, because a work–life imbalance can cause stress and health-related problems among workers.This study examines the relationship between emotional intelligence and work–life balance among police officers, and also the impact of organizational support as a moderator in this relationship.The data were collected from 1566 police officers in Peninsular Malaysia.Data was analyzed using the Partial Least Square (PLS) method. The results showed a significant and positive relationship between emotional intelligence and work–life balance.Organizational support was also found to moderate this relationship. These findings suggest that to achieve a work–life balance, police officers must have emotional intelligence, and the presence of organizational support would strengthen this relationship.Hence, in managing police officers’ work–life balance, it is important to enhance their emotional intelligence and implement organizational support policies.